Feeding trial on the effects of high-protein, low-energy diets on lean meat production in broiler - Abu Jafor Siddik; Md. Aliar Rahman; Rakhi Chowdhury; Khan Md. Shaiful Islam (Veterinary Integrative Sciences)
This study aimed to produce lean meat from broiler chickens fed a high-protein, low-energy diet. For 35 days, 250 straight-run Cobb-500 chicks were arbitrarily assigned to five dietary groups, with 50 birds in each group and 10 birds as replicates per cage. The per-kg diets of the different groups contained 1. Twenty-two percent crude protein (CP), 2,900 kcal metabolizable energy (ME), 2. Twenty-two percent CP and 2,600 kcal ME, 3. Twenty-four percent CP and 2,600 kcal ME, 4. Twenty-six percent CP and 2,600 kcal ME, and 5. Twenty-eight percent CP and 2,600 kcal ME. On the final day, 15 birds from each group were sacrificed to evaluate carcass traits, meat colour, gastrointestinal tract pH, and blood profiles. Group 3 (24% CP and 2,600 kcal ME) achieved a substantially higher weight (1,500 g), consumed more feed (2,445 g), and had a better FCR (1.67) than the other groups (P < 0.05). pH levels tended to be higher in the duodenum in Group 5, whereas Group 3 showed optimal serum albumin, urea, and calcium levels. Compared to the other groups, Group 3 had a higher CP content and redder meat. The dressing yields (without skin) were 58.47, 58.51, 62.06, 59.49, and 60.03% in Groups 1, 2, 3, 4, and 5, respectively, with Group 3 having the highest value (P < 0.05). Muscle fat was lower in Groups 2 and 3, but skin fat was lower in Groups 3 and 4 (P < 0.05), indicating that the possibility of obtaining lean meat was higher in Group 3. Therefore, diets containing 24% CP and 2,600 kcal ME/kg are recommended to farmers for better growth and meat quality (leanness, redness, and low abdominal fat) of broilers